Assessing the impact of moxibustion on colonic mucosal integrity and gut microbiota in a rat model of cerebral ischemic stroke: insights from the “brain-gut axis” theory - Ding, Yi-Xia; Chen, Liang-Liang; Li, Kui-Wu; Zou, Ling; Liao, Lu-Min; Han, Xiao-Yu; OuYang, Jie; Wu, Yue-Ping; Zhang, Wen-Dong; Chu, Hao Ran (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study is to assess the impact of moxibustion on the colonic mucosal barrier and gut microbiota in a rat model of cerebral ischemic stroke (CIS).MethodThe CIS rat model was established using the modified Zea Longa suture method. Successfully modeled rats were randomly allocated into a model group and a moxibustion group, with a sham surgery group serving as the control. The moxibustion group received suspended moxibustion at Dazhui (GV 14), Baihui (GV 20), Fengfu (GV 16), and bilateral Tianshu (ST 25) and Shangjuxu (ST 37) acupoints. Neurological function was assessed using the Longa score, and brain infarct size was assessed through 2,3,5-triphenyl tetrazolium chloride staining. Gut microbiota composition was analyzed using 16S rDNA amplification sequencing. Intestinal mucosal permeability was evaluated using the FITC-Dextran tracer method. The serum ET-1 levels and the expression of Occludin and ZO-1 proteins in colonic tissues were also measured.ResultThe model group exhibited significantly higher Longa scores, larger brain infarct size, and higher serum FITC-Dextran levels and ET-1 levels when compared with the sham surgery group (p < 0.01). The model group demonstrated decreased expression of Occludin and ZO-1 in colonic tissues (p < 0.01) and changes in gut microbiota structure. When compared to the model group, the moxibustion group demonstrated significantly lower Longa scores, smaller brain infarct size, and lower serum FITC-Dextran levels and ET-1 levels (p < 0.05). Furthermore, the moxibustion group demonstrated decreased inflammatory cell infiltration in colonic tissues, increased expression of Occludin and ZO-1 proteins in colonic tissues (p < 0.05), enhanced gut microbiota structure, and a decreased Simpson index (p < 0.05).ConclusionMoxibustion can improve the neurological dysfunction in CIS model rats. The mechanism may be associated with the improvement in gut microbiota dysbiosis, reduction in colonic mucosal permeability, and restoration of intestinal mucosal barrier damage.